Attention please!: Health plan choice and (in-)attention - Tamara Bischof; Michael Gerfin; Tobias Müller (University of Bern, Department of Economics, 2021)
Most studies examining the impact of migrants on crime rates in hosting populations are in the context of economic migrants in developed countries. However, we know much less about the crime impact of refugees in low- and middle-income countries-whose numbers are increasing worldwide. This study examines this issue in the context of the largest refugee group in any country-Syrian refugees in Turkey. Although these refugees are much poorer than the local population, have limited access to formal employment, and face partial mobility restrictions, we find that total crime per person (including natives and refugees) falls due to the arrival of the refugees. This finding also applies to several types of crime; the only exception is smuggling, which increases due to the population influx. We also show that the fall in crime does not result from tighter security; we find no evidence of a change in the number of armed forces (military and civil personnel) in the migrant-hosting regions. We study the role of inattention as a key source of inertia in health plan choices. Our structural model shows that more than 90% of the elderly in Switzerland are inattentive and thus stick to their previous plan. We estimate sizeable switching costs even conditional on attention explaining part of the observed choice persistence. Inattention leads to overspending and generates considerable welfare losses for most consumers. A policy simulation shows that eliminating financially dominated plans from the choice set yields welfare gains for two thirds of individuals.
Keywords: D12; G22; I13; D90; J14; 330; health plan choice; inertia; attention; switching costs; managed competition; elderly